Situation and Perspectives of Intermodal Logistics in Hungary - Zoltan Bokor; Adam Torok (Promet - Traffic&Transportation, 1970)
Logistics has become one of the determining factors inHungarian economic policy. This is supported by the fact thatlogistics has been included into the key programmes of the 2'dHungarian National Development Plan. Intermodallogisticsservices belong to the most important instruments emphasisedby the Hungarian transport policy. Although there have beenseveral improvements in the field of logistics centres and combinedtransport the national intennodallogistics network cannotbe regarded as finished yet. That is why additional investmentsare needed. However, the new developments shall besupported by updated strategic conceptions taking into considerationthe current and future trends in technology and economy,with special regard to changed conditions coming fromjoining the EU This paper aims to analyse the national and internationalbackground of intermodal logistics strategy improvementsand furthermore to draw conclusions on the possibledevelopment directions applicable for specific Hungariancircumstances.